Przyczynek do badań nad aspektem kulturowym Eneidy Iwana Kotlarewskiego w tłumaczeniu Piotra Kuprysia - Czetyrba-Piszczako, Mirosława (Acta Polono-Ruthenica, 2018)
Piotr Kupryś was the first Polish translator to fully translate two classical works fundamental for Ukrainian literature. These were: Kobzar by Taras Shevchenko and Eneida by Ivan Kotliarevsky. Kotliarevsky’s Eneida is a vivid example of adapting diverse elements of oral folklore culture in modern Ukrainian literature. The article analyses types of translation procedures the translator applied when dealing with cultural context. Generally speaking, Kupryś followed two strategies of rendering cultural elements: domestication – in order to adapt the target text to target readers’ knowledge; as well as foreignisation with explanation – thanks to which he enriched target readers’ knowledge about reality and culture of the source text.